Competence Assessment in Dementia - European Dementia Consensus Network (Springer Vienna : Imprint: Springer, 2008)
1 Dementia and related disorders affect the suffer- minimal standards of care for people with dementia , ers' ability to perform activities of daily living and the improvement of access to diagnosis and treat- 2 3 to make appropriate decisions about various issues ment , ethical issues related to research in dementia , relevant to their life. While there is no disagreement the problems related to severe dementia, stigma and about these facts there is little clarity and even less social exclusion of people with dementia, assessment consensus about the ways in which competence to of outcome of treatment of dementia and the asse- make decisions should be assessed in daily practice ment of competence of people with dementia. The - nor is there agreement about the levels of compe- work to develop consensus on the latter subject lead, tence at which it is in the best interest of the people inter alia to the production of this volume. with dementia to have a guardian and receive legal In its work the EDCON Steering committee - protection against abuse and other mistreatment. lects areas on which it will concentrate and desig- In daily clinical practice there is a large heterogene- nates a coordinator for the work on each of those.